2021
DOI: 10.1016/j.jceh.2021.01.007
|View full text |Cite|
|
Sign up to set email alerts
|

WITHDRAWN: Dyslipidemia Increases the Risk of Severe COVID-19: A Systematic Review, Meta-analysis, and Meta-regression

Abstract: Objective This systematic review and meta-analysis aimed to evaluate whether dyslipidemia affects the mortality and severity of COVID-19, we also aimed to evaluate whether other comorbidities influence the association. Methods A systematic literature search using PubMed, Embase, and EuropePMC was performed on 8 October 2020. This study's main outcome is a poor composite outcome, comprising of mortality and severe COVID-19. Results There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
1
14
0
1
Order By: Relevance
“…Interestingly, all of these had severe disease and/or comorbidities (i.e., diabetes, hypertension or cardiovascular disorders, chronic lung disease and HIV infection, dyslipidemia). These observations are in agreement with previous studies that reported an association between SARS-CoV-2 RNA persistence with severe disease [15,21] and comorbidity [19,[22][23][24] following remission of the acute symptoms. More recently, Jacobs et al highlighted the association between SARS-CoV-2 plasma viremia and ICU admission [25], and Tokuyama et al described SARS-CoV-2 persistence in intestinal enterocytes up to 7 months after symptoms resolutions [26].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, all of these had severe disease and/or comorbidities (i.e., diabetes, hypertension or cardiovascular disorders, chronic lung disease and HIV infection, dyslipidemia). These observations are in agreement with previous studies that reported an association between SARS-CoV-2 RNA persistence with severe disease [15,21] and comorbidity [19,[22][23][24] following remission of the acute symptoms. More recently, Jacobs et al highlighted the association between SARS-CoV-2 plasma viremia and ICU admission [25], and Tokuyama et al described SARS-CoV-2 persistence in intestinal enterocytes up to 7 months after symptoms resolutions [26].…”
Section: Discussionsupporting
confidence: 93%
“…The disease severity was higher in the overweight and obese categories and male gender in current study encompassed a greater percentage in these categories, this finding is also supported by previous studies. 13,14 The three divisions of participants according to age was group 1 with ages between 1 -30 years, group 2 with ages between 31 -60 years and group 3 with ages between 61 -90 years. The major portion totaling 84 participants out of 130 in group 1 were underweight or normal weight, whereas 46 out of 130 were overweight and obese.…”
Section: Resultsmentioning
confidence: 99%
“…Of the risk factors for COVID-19 considered in this study, dyslipidemia was the most prevalent, affecting nearly four-fifths of shift workers (77.9%). A meta-analysis by Atmosudigdo et al (2021) 17 evaluating 9 studies with 3663 patients, found that subgroup analysis showed that dyslipidemia was associated with severe COVID-19 (RR: 1.39; 95% IC = 1.03-1.87; I2: 57.4%, p =.029). And the association was stronger in older patients, male, and hypertensive 17 .…”
Section: Discussionmentioning
confidence: 99%